Discovery of nitrate–CPK–NLP signalling in central nutrient–growth networks - Liu, Kun-hsiang; Niu, Yajie; Konishi, Mineko; Wu, Yue; Du, Hao; Sun Chung, Hoo; Li, Lei; Boudsocq, Marie; McCormack, Matthew; Maekawa, Shugo; Ishida, Tetsuya; Zhang, Chao; et al. (Nature (London), 2017)
Nutrient signalling integrates and coordinates gene expression, metabolism and growth. However, its primary molecular mechanisms remain incompletely understood in plants and animals. Here we report unique Ca 2+ signalling triggered by nitrate with live imaging of an ultrasensitive biosensor in Arabidopsis leaves and roots. A nitrate-sensitized and targeted functional genomic screen identifies subgroup III Ca 2+ -sensor protein kinases (CPKs) as master regulators that orchestrate primary nitrate responses. A chemical switch with the engineered mutant CPK10(M141G) circumvents embryo lethality and enables conditional analyses of cpk10 cpk30 cpk32 triple mutants to define comprehensive nitrate-associated regulatory and developmental programs. Nitrate-coupled CPK signalling phosphorylates conserved NIN-LIKE PROTEIN (NLP) transcription factors to specify the reprogramming of gene sets for downstream transcription factors, transporters, nitrogen assimilation, carbon/nitrogen metabolism, redox, signalling, hormones and proliferation. Conditional cpk10 cpk30 cpk32 and nlp7 mutants similarly impair nitrate-stimulated system-wide shoot growth and root establishment. The nutrient-coupled Ca 2+ signalling network integrates transcriptome and cellular metabolism with shoot–root coordination and developmental plasticity in shaping organ biomass and architecture. In response to nitrate, Ca 2+ -sensor protein kinases (CPKs) act as master regulators to coordinate downstream signalling responses that are essential for shoot growth and root establishment in Arabidopsis . How nitrates stimulate roots and shoots In plants, nutrient-associated signals affect gene expression, metabolism and ultimately growth, yet many of the molecular components connecting these signals to gene expression remain unknown. Jen Sheen and her team report that, in response to nitrate, the Ca 2+ -sensor protein kinases (CPKs) act as master regulators to coordinate downstream responses. Specifically, CPK phosphorylates the NIN-like protein (NLP) transcription factor, resulting in the reprogramming of genes that encode additional transcription factors, transporters and proteins that regulate nitrate metabolism, among others. This pathway is essential for nitrate-stimulated shoot growth and root establishment.